Urgency Of Filling The Legal Gaps in Preventing Contract Marriages - Ubaidilah Ishaq; Riswadi Riswadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This research examines the issue of contract marriages in Indonesia, focusing on the legal gaps that result in uncertainty and negative impacts on women and children. Despite the increasing prevalence of contract marriages, there is no clear regulation in the Marriage Law or criminal law governing this practice, placing individuals involved in vulnerable positions, especially women who are often victims of exploitation and violence. Through an analysis of existing regulations and their impact on social structures, this study highlights the need for legal reform, including the revision of Law No. 1 of 1974 on Marriage and the formulation of specific legislation to prohibit contract marriages. This research also recommends strengthening the oversight system, law enforcement, and providing protection services for women and children to create a safer and more equitable environment.